(untitled) (Research, Society and Development, 2022)
Cost control is a determining factor in order to avoid budgetary unforeseen events and increase profitability in Civil works. Being, efficient budgeting, one of the main success factors in civil construction. Some instruments, such as the Pareto Diagram or ABC curve, appear in order to assist the cost management process. Thus, this research seeks to carry out the cost analysis of a residential development located in the municipality of Salinópolis-PA, through the application of the ABC curve to data from the global budget of the Civil work. The methodology was divided into 5 stages, starting with the definition of the unitary and total costs of each item, hierarchy of the items in decreasing form of total cost, calculation of the individual and accumulated percentages of composition of the global budget, classification of the items in bands A, B and C, representation of the results through the elaborated curve and discussion of the data. 303 items were identified, distributed among materials and services, 8% classified in range A, 16% in range B and 76% in C. Based on the results obtained, this tool shows itself as a simple and satisfactory methodology for carrying out the control of construction costs, which can be applied in different types of projects and in different phases.